Potential positive and negative autoregulation of p60c-src by intermolecular autophosphorylation. - Cooper, J A (1988)
The product of the protooncogene c-src is a protein-tyrosine kinase, p60c-src, that is normally inhibited by phosphorylation at a tyrosine residue close to the C terminus (Tyr-527). If activated by dephosphorylation of Tyr-527, or by other means, p60c-src becomes phosphorylated at a tyrosine residue in the catalytic domain (Tyr-416). To test whether either or both of these tyrosines can be phosphorylated by p60c-src itself, we have created four mutations in c-src. One mutant product can receive but cannot donate phosphate, and other mutants are capable of catalysis but lack phosphorylation sites. The mutant genes were expressed singly or in combination in yeast. Analysis of the phosphorylation of mutant p60c-src in the yeast cells and in immunoprecipitates showed that p60c-src molecules can phosphorylate each other at Tyr-416 and -527. Prohibiting intramolecular phosphorylation had little effect on reaction rates and extents, suggesting that intermolecular phosphorylation predominates. If the same situation pertains in the milieu of the vertebrate fibroblast, phosphorylation of one p60c-src by another at Tyr-416 or -527 could permit positive or negative autoregulation.